Clinical variable-based cluster analysis identifies novel subgroups with a distinct genetic signature, lipidomic pattern and cardio-renal risks in Asian patients with recent-onset type 2 diabetes - Wang, J (Springer Science and Business Media LLC, 2023)
10.1007/s00125-022-05741-2